2018
DOI: 10.1042/bst20170519
|View full text |Cite
|
Sign up to set email alerts
|

The role of Rac in tumor susceptibility and disease progression: from biochemistry to the clinic

Abstract: The family of Rho GTPases are involved in the dynamic control of cytoskeleton reorganization and other fundamental cellular functions, including growth, motility, and survival. Rac1, one of the best characterized Rho GTPases, is an established effector of receptors and an important node in signaling networks crucial for tumorigenesis and metastasis. Rac1 hyperactivation is common in human cancer, and could be the consequence of overexpression, abnormal upstream inputs, deregulated degradation, and/or anomalous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 106 publications
0
31
0
Order By: Relevance
“…P-Rex1 is activated by human epidermal growth factor receptor (HER2) and GPCRs, such as the chemokine receptor CXCR4 in breast cancer, and overexpressed in ER and HER2 positive luminal A and B breast cancer tissues compared to normal breast tissue. P-Rex1 expression was actually low in triple-negative primary tumors but was upregulated in distant metastases (Marotti et al, 2017;Casado-Medrano et al, 2018;Kazanietz et al, 2018). Furthermore, demethylation in the PREX promoter has been associated with breast cancer mortality (Montero et al, 2011).…”
Section: Targeting Vav1/2/3mentioning
confidence: 99%
See 1 more Smart Citation
“…P-Rex1 is activated by human epidermal growth factor receptor (HER2) and GPCRs, such as the chemokine receptor CXCR4 in breast cancer, and overexpressed in ER and HER2 positive luminal A and B breast cancer tissues compared to normal breast tissue. P-Rex1 expression was actually low in triple-negative primary tumors but was upregulated in distant metastases (Marotti et al, 2017;Casado-Medrano et al, 2018;Kazanietz et al, 2018). Furthermore, demethylation in the PREX promoter has been associated with breast cancer mortality (Montero et al, 2011).…”
Section: Targeting Vav1/2/3mentioning
confidence: 99%
“…The pivotal role of Rac and Cdc42 in multiple cancers has been extensively reviewed by us and others (Pai et al, 2010;Mack et al, 2011;Stengel and Zheng, 2011;Wertheimer et al, 2012;Bid et al, 2013;Kazanietz and Caloca, 2017;Casado-Medrano et al, 2018;Maldonado and Dharmawardhane, 2018;De et al, 2019). In addition, the related Rho GTPase Rho has also been implicated in tumorigenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our work identified Rac1 and Cdc42 hyperactivation in aggressive androgen-insensitive DU145 and PC3 prostate cancer cell lines. These proteins and their regulators are known to play important roles in the progression of cancer and are therefore of interest as potential therapeutic targets [3]. We have also demonstrated that targeting P-Rex1, a previously identified therapeutic target candidate, is unlikely to have an impact on Rac1 activation status, migration or invasion in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 67%
“…One is that multiple GEFs are required for maintaining Rac1-GTP and Cdc42-GTP in these cells, and thus silencing single GEFs is insufficient to cause an effect. We cannot rule out that a Rac-GEF not included in our screen could be involved, albeit a less likely possibility because our analysis encompasses the majority of known Rac-GEFs [3]. However, it is quite remarkable that no Dbl or DOCK family GEFs were identified in our proteomics analysis using a nucleotide free Rac1 bait, which is designed to pull-down Rac1 associated GEFs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation